The Standard Form of a Quadratic Function:
![\text{ y = ax}^2\text{ + }bx\text{ + c}](https://img.qammunity.org/2023/formulas/mathematics/college/6rl1dq204liv19ltfa6gnq5j958giqp3ug.png)
Using the given points (-1,5), (0,3), and (3,9), let's substitute each point to the equation.
At (-1,5):
![\text{ y = ax}^2\text{ + bx + c }\rightarrow5=a(-1)^2\text{ + b(-1) + c}](https://img.qammunity.org/2023/formulas/mathematics/college/gje7qjee1zhxg7b2hmdbds0b4jbp5kj996.png)
![\text{ 5 = a - b + c}](https://img.qammunity.org/2023/formulas/mathematics/college/62rnlw034q81v1tc40za5s4ge3lkvosgnf.png)
At (0,3):
![\text{ y = ax}^2\text{ + bx + c }\rightarrow3=a(0)^2\text{ + b(0) + c}](https://img.qammunity.org/2023/formulas/mathematics/college/mj8i4dxgwe298dfz4yg5ya9sjuksxumnlo.png)
![\text{ 3 = c}](https://img.qammunity.org/2023/formulas/mathematics/college/hhodemxbu5o8t4jbitvfofo8eydgo5j15z.png)
At (3,9):
![\text{ y = ax}^2\text{ + bx + c }\rightarrow9=a(3)^2\text{ + b(3) + c}](https://img.qammunity.org/2023/formulas/mathematics/college/qv9bstdi85jasa17ikv7vebxv80c43i3fw.png)
![\text{ 9 = 9a + 3b + c}](https://img.qammunity.org/2023/formulas/mathematics/college/jc9ysmq7ph5fehzlbv8a8v3sm2ltjn0rr5.png)
We now get these equations:
5 = a - b + c ; 3 =c; 9 = 9a + 3b + c
Let's determine the value of a, b and c. We get,
Substituting 3 = c to 5 = a - b + c,
![\text{ 5 = a - b + c }\rightarrow\text{ 5 = a - b + 3 }\rightarrow\text{ a - b = 2}](https://img.qammunity.org/2023/formulas/mathematics/college/7uc3679ogqluvqu11p5bjmv23tplb2koui.png)
![\text{ b = a - 2}](https://img.qammunity.org/2023/formulas/mathematics/college/cs0ou1fq5b6elpqg88xxxa052m4k2qi578.png)
Let's substitute 3 = c and b = a - 2 to 9 = 9a + 3b + c,
![\text{ 9 = 9a + 3b + c }\rightarrow\text{ 9 = 9a + 3(a-2) + 3}](https://img.qammunity.org/2023/formulas/mathematics/college/w37rbh5tbc2q4gmvoojyk90cjglmpqd4te.png)
![\text{ 9 = 9a + 3a - 6 + 3 }\rightarrow\text{ 12a = 9 + 6 - 3 }\rightarrow\text{ 12a = 12}](https://img.qammunity.org/2023/formulas/mathematics/college/le9i060k1hzjm3bm0969j913xa9jgmpkdg.png)
![\text{ a = }(12)/(12)\text{ = 1}](https://img.qammunity.org/2023/formulas/mathematics/college/vxs1f0m1jmlu09ijvqpqf24d1o3c79kopb.png)
Since a = 1, let's solve for the value of b which is b = a - 2.
![\text{ b = a - 2 }\rightarrow\text{ b = 1 - 2}](https://img.qammunity.org/2023/formulas/mathematics/college/kzk1c11mxrutie9u5420g59ax7ws3xut2k.png)
![\text{ b = -1}](https://img.qammunity.org/2023/formulas/mathematics/college/zjzsyf7ngecij5rjmxrg0ltiedl67z65gx.png)
Since we've identified that a = 1, b = -1 and c = 3, let's substitute the values to the standard form of a quadratic function to be able to make the equation.
![\text{ y = ax}^2\text{ + bx + c }\rightarrow y=(1)x^2\text{ + (-1)x + (3)}](https://img.qammunity.org/2023/formulas/mathematics/college/lc42uudsvoor63ef1wmrm17ypi92ix5ip9.png)
![\text{ y = x}^2\text{ - x + 3}](https://img.qammunity.org/2023/formulas/mathematics/college/acnzsjtvdego1hjm41aup9sa0ka5mt2rpe.png)
Therefore, the quadratic function in a standard form whose graph passes through the given points (-1,5), (0,3), (3,9) is y = x^2 - x + 3.